XeUS: A second-generation automated open-source batch-mode clinical-scale hyperpolarizer - Birchall, Jonathan R.; Irwin, Robert K.; Nikolaou, Panayiotis; Coffey, Aaron M.; Kidd, Bryce E.; Murphy, Megan; Molway, Michael; Bales, Liana B.; Ranta, Kaili; Barlow, Michael J.; Goodson, Boyd M.; Rosen, Matthew S.; et al. (Journal of magnetic resonance (1997), 2020)
[Display omitted] •Automated batch-mode clinical-scale xenon-129 SEOP hyperpolarizer.•XeUS second-generation device.•Near unity hyperpolarized Xenon-129 contrast agent.•Cryogen-free production cycle of 1 h. We present a second-generation open-source automated batch-mode 129Xe hyperpolarizer (XeUS GEN-2), designed for clinical-scale hyperpolarized (HP) 129Xe production via spin-exchange optical pumping (SEOP) in the regimes of high Xe density (0.66–2.5 atm partial pressure) and resonant photon flux (~170 W, Δλ = 0.154 nm FWHM), without the need for cryo-collection typically employed by continuous-flow hyperpolarizers. An Arduino micro-controller was used for hyperpolarizer operation. Processing open-source software was employed to program a custom graphical user interface (GUI), capable of remote automation. The Arduino Integrated Development Environment (IDE) was used to design a variety of customized automation sequences such as temperature ramping, NMR signal acquisition, and SEOP cell refilling for increased reliability. A polycarbonate 3D-printed oven equipped with a thermo-electric cooler/heater provides thermal stability for SEOP for both binary (Xe/N2) and ternary (4He-containing) SEOP cell gas mixtures. Quantitative studies of the 129Xe hyperpolarization process demonstrate that near-unity polarization can be achieved in a 0.5 L SEOP cell. For example, %PXe of 93.2 ± 2.9% is achieved at 0.66 atm Xe pressure with polarization build-up rate constant γSEOP = 0.040 ± 0.005 min−1, giving a max dose equivalent ≈ 0.11 L/h 100% hyperpolarized, 100% enriched 129Xe; %PXe of 72.6 ± 1.4% is achieved at 1.75 atm Xe pressure with γSEOP of 0.041 ± 0.001 min−1, yielding a corresponding max dose equivalent of 0.27 L/h. Quality assurance studies on this device have demonstrated the potential to refill SEOP cells hundreds of times without significant losses in performance, with average %PXe = 71.7%, (standard deviation σP = 1.52%) and mean polarization lifetime T1 = 90.5 min, (standard deviation σT = 10.3 min) over the first ~200 gas mixture refills, with sufficient performance maintained across a further ~700 refills. These findings highlight numerous technological developments and have significant translational relevance for efficient production of gaseous HP 129Xe contrast agents for use in clinical imaging and bio-sensing techniques.